Avoiding debt traps Fiscal consolidation, financial backstops and structural reforms - Padoan, Pier Carlo (OECD Publishing, 2012)
In this article we develop a simple and stylised analytical framework, which is both tractable and feasible to estimate, capturing several key dimensions of the sovereign debt crisis in Europe. We use it to examine if and how a combination of fiscal consolidation, structural reform and financial backstops can help countries, notably the southern euro-area countries, to escape from the debt trap. Our analysis confirms that the loss of fiscal policy space in countries trapped in bad dynamics inevitably requires that fiscal action be directed towards consolidation despite some output loss in the short run. In particular, reducing debt levels breeds stronger growth and results in lower sovereign risk premia. We identify also a very important role for structural reform to help countries escape from bad dynamics. Last but not least, we find that financial backstops are helpful, but only to "buy time". This additional time must be used productively, for fiscal consolidation and structural reforms to bear fruit as well as to make progress with institutional reforms of the European monetary union